THE ROLE OF RELIGIOUS BELIEFS AND PARENTING STYLES ON MORAL VALUES AMONG UNIVERSITY STUDENTS - Hafiz Umer Basheer; Umama Mushtaq; Dr. Haziq Mehmood; Nazar Abbas (International Journal of Contemporary Issues in Social Sciences, 2024)
The purpose of this study was to find out the relationship of morality, religion, and parenting styles among university students in Lahore, Pakistan. A sample of 251 students with an age range of 17 to 40 years old was taken. It consists of 119 women and 132 men was taken. Sample was collected via convenient sampling strategy in public and private universities. Morality Scale (Hofstee et al., 1992), The Santa Clara Strength of Religious Faith Questionnaire (SCSRFQ) (Plante & Boccaccini, 1997), Perceived Dimensions of Parenting Scale (PDPS) (Robinson et al., 1995) were used to collect data for assessment. Results of correlation analysis showed significant and positive correlation between religion and parenting style. Moreover, there was highly significant and negative relationship between morality and parenting style (Aggressive parenting). Qualification has significant positive relationship with morality and controlling parenting style. There were significant gender differences in terms of morality and parenting styles with small effect size. There were significant differences among CGPA (low and high achievers) in terms of religion in university students. There were differences at level of education (undergraduate and graduates) in terms of morality and controlling parenting style. On the other hands, there were non-significant relation of morality with religion. Graduated students found to have high morality as compared to bachelors’ students. This research is beneficial for university students to understand the role of morality, religion and the importance of parenting styles in predicting high and low moral values.